2020
DOI: 10.1002/nop2.513
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' perspectives on technical skill requirements in primary and tertiary healthcare services

Abstract: Aim To explore nurses' perspectives on technical skill requirements in primary and tertiary healthcare services and their perspectives on where students should learn these skills. Design The study was conducted in Norway and had a cross‐sectional, multicentre, descriptive design. Methods We used a questionnaire to explore registered nurses and intellectual disability nurses' perspectives on technical skill requirements and learning ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Still, integrating physical assessment subjects in the undergraduate nursing curriculum remains challenging (Byermoen et al, 2021; Douglas et al, 2015). A recent study found that nurses perceive that students should learn both basic and advanced technical skills in the educational institution and then practise further in clinical practice (Leonardsen et al, 2020). In contrast, nurses report to receive training in technical procedures such as handling of ventilators, tracheostomia, palliation or dialysis, at work (Leonardsen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Still, integrating physical assessment subjects in the undergraduate nursing curriculum remains challenging (Byermoen et al, 2021; Douglas et al, 2015). A recent study found that nurses perceive that students should learn both basic and advanced technical skills in the educational institution and then practise further in clinical practice (Leonardsen et al, 2020). In contrast, nurses report to receive training in technical procedures such as handling of ventilators, tracheostomia, palliation or dialysis, at work (Leonardsen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Supervisors described that students needed to learn both basic and advanced technical skills, as well as both general and arena specific skills when in clinical practice. A recent study found that RNs and IDNs perceive that students should learn both basic and advanced technical skills in the university college, and then practice further in clinical practice [ 28 ]. Moreover, another study showed that RNs in primary healthcare receive training in specific technical procedures such as handling of ventilators, tracheostomia, palliation or dialysis [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The supervisors expected the university college to provide students with both theoretical knowledge and practical training relevant for the specific clinical placement. In a recent study across primary and tertiary healthcare in the same county, we found that RNs/IDNs perceived that students should learn technical skills in the university college first, and then get more training in clinical placement [ 32 ]. This was supported by findings from the focus group discussions in the current study.…”
Section: Discussionmentioning
confidence: 99%